ANALISIS FAKTOR.FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM MENGGUNAKAN KERETA API SEBAGAI MODA TRANSPORTASI DI KABUPATEN JEMBER - Supriadi Supriadi; Salahuddin Salahuddin (RELASI : JURNAL EKONOMI, 2012)
The lndonesian Railway Transportation Company (PT KA\ is one of the statecompanies which is engaged in transporlation mode, ln order to meet the needs ofconsumers, the company considers several factors that cause consumers interest in usingthe railway as a means of transportation facilities.Ihe purposes of this research are: a). To determine the effect of simultaneously orpartially independent factors such as the safety and security (x1), the convenience (x2),the ticket prices (x3), the railway station area (x4) and the timeliness (x5) on consumersbehavior in using this mode of transpoftation (Y) in Jember, b). To find the dominant,independent factors that influence consumers behavior in the use of this mode oftransportation (Y) in Jember.Based on the analysis, it is concluded that the simultaneous independent factors ofsafety and the security factors (x1), the convenience factors (x2), ticket prices factors (x3),the railway station area factors (x4) and the timeliness factors (x5) have the significanteffects on the dependent variable (Y) for the consumers behavior in using of the railwaytransporlation as their mode However. partially, independent factors of safety andsecurrty (x1), the convenience (x2), the ticket price (x3). the railway station area (x4)influence significantly to the consumers behavior while the trneltness factor (x5) has nosi gnific ant infl u ences./t ls suggesfed that The lndonesian Railway Transpoftation Company (Pf KN).especially the Operation Area lX ( DAOP lX) of Distrtct Jember pay more attentton andincrease the return on some of the factors that infltience corsr/,?ers behavior a-s weil asconsider other factors in addition to the above factors that also influence colrsu,r?ershehavior.